Health and african-brazilian ethnicity research group (HABERG) - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2002)
Since 1994, the Health and African-Brazilian Ethnicity Research Group is focused on the social determinants of health inequalities. The group was created and is directed by Isabel Cruz, RN, PhD It is based in the Medical-Surgical Nursing Department, Fluminense Federal University (RJ, Brazil). Its aims were to undertake multi-disciplinary social and health science research to advance the understanding of the social processes, particularly the racism, which underlie and mediate socio-economic inequalities in health and to advance the methodology of health inequalities research.These aims are been taking forward through two projects. The project related to the nursing diagnosis chronic low self-esteem  and the nursing intervention cultural brokerage is multi-disciplinary, involving collaborators from arts (music, dance, painting, literature), economics, history, psychology, social policy and sociology. The other project is related to the nursing diagnoses and interventions to the hypertensive client and his family. Both projects have a focus on racism and socio-economic inequalities in health, addressing for example ethnic and gender inequalities which are not yet on the scientific and policy agenda of public health.Communication with the users of research has been a priority for the HABERG, which was linked regularly to over 500 users in and beyond Brazil by the NEPAE-NESEN Eletronic Newsletter which provides updates on HABERG activities, researches, and its policy implications. The information on the website (www.uff.br/nepae/NESEN.htm) provides a record of the research group activities.Publications: all HABERG newsletter articles and research reports are displayed on the website www.uff.br/nepae or www.uff.br/nepae/NESEN.htm